Analysis of Balanced Scorecard Implementation in Measuring Company Performance at PT. SBC Berkah Bersama - Ayu Wulan Dari; Yuniep Mujati Suaidah (Proceeding International Conference on Digital Education and Social Science, 2025)
This study aims to analyze the implementation of the Balanced Scorecard (BSC) in measuring company performance at PT. SBC Berkah Bersama, a multi-unit retail company operating in East Java. This research employs a descriptive qualitative approach to provide a comprehensive overview of company performance based on the four Balanced Scorecard perspectives: financial, customer, internal business process, and learning and growth. Data collection techniques include in-depth interviews with management, direct observation of operational activities, documentation review, and supporting questionnaires distributed to customers and employees. The results indicate that the implementation of the Balanced Scorecard at PT. SBC Berkah Bersama assists management in evaluating company performance more comprehensively, not only from a financial perspective but also in terms of service consistency, operational effectiveness, customer satisfaction, and human resource development across business units. Although financial ratio analysis is not conducted quantitatively, the descriptive use of financial indicators still provides strategic information for managerial decision-making. This study concludes that the Balanced Scorecard is a relevant and applicable performance measurement framework for medium-scale multi-unit retail companies and can support strategic alignment and sustainable performance improvement.